Model Komunikasi Dakwah Jamaah Tabligh - Saepuloh, Ujang (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2009)
Jamaâah Tabligh constitutes one of daâwah organizations in Indonesian that has many unique characteristics. Besides its daâwah movement that different of organisational daâwah in a general way, this organisation also has typical symbols of its fellow men. Aspects that can be recognized from this jamaâah at least cover three: (1) daâwah movement pattern named khuruj, which is sticking out, far from home, (2) configurational figures that do ever pet beard, putting on elongated cloth, bounding up head with cloth and always use pants upon ankle, (3) daâwah communication models that by large develope: daâwatul-ifrodi communication model, daâwatul-ijtimaâi communication model, daâwatul khususi wal-umumi communication model.